Characterization of fusarium semitectum isolates from vegetable fruits - Latiffah, Z.; Nurul Huda, M.S.; Tengku Ahmad Akram, T.M.A (Universiti Kebangsaan Malaysia, 2013)
Fusarium semitectum is a widespread species occurring in various types of substrate. Fifteen F. semitectum isolates were recovered from several types of vegetable fruits showing fruit rot symptoms, namely long bean (Vigna sesquilpedalis), okra (Abelmoschus esculentus), loofa (Luffa acutangula), bitter gourd (Momordica charantia), cucumber (Cucumis sativus) and green chilli (Capsicum annum). The identification of the F. semitectum isolates was based on morphological characteristics of macroconidia and microconidia, presence of mesoconidia and colony pigmentation. The isolates were then characterized using vegetative compatibility group (VCG) and sequencing of translation elongation factor-1α gene (TEF-1α). From VCG analysis, 11 isolates were assigned to six VCGs and another four isolates were self-incompatible. The results of the phylogenetic analysis using TEF-1α sequences showed that the isolates were phyogenetically distinct although the morphological characteristics were very similar and generally the grouping of the isolates was not according to the host. Both VCG and phylogenetic analyses indicated that F. semitectum isolates from vegetable fruits were highly variable which suggested that the isolates belong to a species complex.